Less improvement following meniscal repair compared with arthroscopic partial meniscectomy: a prospective cohort study of patient-reported outcomes in 150 young adults at 1- and 5-years' follow-up. (8th October 2021) - Pihl, Kenneth; Englund, Martin; Christensen, Robin; Lohmander, L Stefan; Jørgensen, Uffe; Viberg, Bjarke; Fristed, Jakob Vium; Thorlund, Jonas B
Abstract : Background and purpose — Meniscal repair may reduce long-term risk of knee osteoarthritis compared with arthroscopic partial meniscectomy (APM), whereas patient-reported outcomes may be poorer at short term than for APM. We compared patient-reported outcomes in young adults undergoing meniscal repair or APM up to ∼5 years after surgery. Patients and methods — We included 150 patients aged 18–40 years from the Knee Arthroscopy Cohort Southern Denmark (KACS) undergoing meniscal repair or APM. Between-group differences in change in a composite of 4 of 5 Knee injury and Osteoarthritis Outcome Score (KOOS) subscales (pain, symptoms, sport and recreation, and quality of life—KOOS4 ) from baseline, 12, and 52 weeks, and a median of 5 years (range 4–6 years) were analyzed using adjusted mixed linear models, with 52 weeks being the primary endpoint. Results — 32 patients had meniscal repair (mean age 26 [SD 6]), and 118 patients underwent APM (mean age 32 [SD 7]). The repair and APM groups improved in KOOS4 from before to 52 weeks after surgery (least square means 7 and 19, respectively; adjusted mean difference –12, [95% CI –19 to –4] in favor of APM). Both groups improved further from 52 weeks to 5 years after surgery with the difference in KOOS4 scores between the groups remaining similar. Interpretation — Patients having meniscal repair experienced less improvements in patient-reported outcomes from baseline to 52 weeks and 5 years post-surgery. The findings highlight the need for randomized trials comparing these interventions in terms of patient-reported outcomes and knee OA development.